2011
DOI: 10.1371/journal.pgen.1001385
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Chk2 and Mus81 Leads to Impaired Lymphocytes Development, Reduced Genomic Instability, and Suppression of Cancer

Abstract: Chk2 is an effector kinase important for the activation of cell cycle checkpoints, p53, and apoptosis in response to DNA damage. Mus81 is required for the restart of stalled replication forks and for genomic integrity. Mus81Δex3-4/Δex3-4 mice have increased cancer susceptibility that is exacerbated by p53 inactivation. In this study, we demonstrate that Chk2 inactivation impairs the development of Mus81Δex3-4/Δex3-4 lymphoid cells in a cell-autonomous manner. Importantly, in contrast to its predicted tumor sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Interestingly, our results also showed that CHK2 inhibitor could slightly aggravating Mus81 deficiency-induced S-phase arrest and apoptosis in response to EPI. These data was consistent with the results from a recent study, which showing that dual inactivation of CHK2 and Mus81 leads to cell death of lymphoid cells despite the underlying mechanism remaining unknown [34]. Our western blot results subsequently indicated that the activity of CHK1 pathway was slightly elevated in Mus81-inhibited HepG2 cells after CHK2 inhibition, thereby promoting the activity of p53, Bax, and Caspase-3, which might be the mechanisms underlying the deteriorative S-phase arrest and apoptosis induced by CHK2 inhibition in Mus81 depleted HCC cells.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our results also showed that CHK2 inhibitor could slightly aggravating Mus81 deficiency-induced S-phase arrest and apoptosis in response to EPI. These data was consistent with the results from a recent study, which showing that dual inactivation of CHK2 and Mus81 leads to cell death of lymphoid cells despite the underlying mechanism remaining unknown [34]. Our western blot results subsequently indicated that the activity of CHK1 pathway was slightly elevated in Mus81-inhibited HepG2 cells after CHK2 inhibition, thereby promoting the activity of p53, Bax, and Caspase-3, which might be the mechanisms underlying the deteriorative S-phase arrest and apoptosis induced by CHK2 inhibition in Mus81 depleted HCC cells.…”
Section: Discussionsupporting
confidence: 93%
“…Broadly defined as ‘checkpoint abrogation’, this strategy relies on the premise that pharmacologic inhibition of Chk2 (and Chk1) may prevent cell cycle arrest in response to DNA damage, and thus sensitize tumor cells to apoptosis (44). While validating Chk2 as an important cancer therapeutic target (45), the data presented also anticipate a broader role of this pathway in tumor progression, via exploitation of the survivin network. Mechanistically, this may involve Chk2-mediated release of cytoprotective survivin from its mitochondrial stores during DNA damage (18), coupled with efficient DSB sensing via phosphorylation of survivin-ΔEx3 (this study).…”
Section: Discussionmentioning
confidence: 73%
“…Accordingly, decreased levels of MUS81 expression have been found in hepatic metastasis and correlated with poor cancer prognosis [43] (Table 2 ). A role for MUS81 in tumorigenesis is further supported by evidence of a synergistic effect with inactivation of p53 and, on the other hand, suppression by inactivating CHK2 [44]. This all together suggests MUS81 to be a potential target for cancer therapy.…”
Section: Introductionmentioning
confidence: 81%